Effect of microwave sintering on density, microstructural and magnetic properties of pure strontium hexaferrite at low temperatures and heating rate - Matran, Wail M.; Mustapha, Mazli; Nor, Mohd Faizairi; Mustapha, Faizal; Alakbari, Fahd Saeed; Al-shawesh, Gamal; Bawahab, Mohammed (Elsevier, 2024)
In recent decades, the rising demand for permanent magnetic materials has driven manufacturers to explore substitutes for rare earth elements in response to their fluctuating prices and negative environmental impact. M-type hexaferrites considered as good alternatives and studies have focused on enhancing their magnetic and structural properties through various approaches. In this study, new approach using low heating rate microwave sintering has been applied to investigate the changes on density, microstructure, and magnetic properties of strontium hexaferrite from core to surface. Sintering temperatures of 950 °C, 1000 °C, 1050 °C, and 1100 °C with 10 °C/minute heating rate were applied accordingly. The bulk density, FESEM, XRD and VSM tests were conducted to study materials’ properties. The outcomes of the study showed exponential relationship between density and sintering temperature reaching optimum value of 91.4 % at 1050 °C and then declined slightly at observed to analysis confirmed the magnetoplumbite structure P63/mmc in all samples and high crystallized structure at 1050 °C, with the occurrence of α-Fe2O3 at 1100 °C. Grain growth and crystallization observed to increase at higher sintering temperature with agglomeration while denser and melted boundaries at lower temperatures. Magnetic properties especially remanence magnetization Mr and saturation magnetization Ms fluctuated with sintering temperature achieving optimum values of 28.188 emu/g and 55.622 emu/g at 1000 °C respectively. Coercivity Hc and magnetic energy density BH max recorded optimum values at 1050 °C. The findings emphasize the critical role of microwave sintering in tailoring the properties of strontium hexaferrite for magnetic applications.